Model-free novelty-based diffusion MRI - Golkov, Vladimir; Sprenger, Tim; Sperl, Jonathan; Menzel, Marion; Czisch, Michael; Saemann, Philipp; Cremers, Daniel (Proceedings - International Symposium on Biomedical Imaging, 2016)
Many limitations of diffusion MRI are due to the instability of the model fitting procedure. Major shortcomings of the model-based approach are a partial information loss due to model simplicity, long scan time requirements due to fitting instability, and the lack of knowledge about how the parameters of a given model would respond to previously unseen microstructural changes, possibly failing to detect certain previously unseen pathologies. Here we show that diffusion MRI pathology detection is feasible without any models and without any prior knowledge of specific pathological changes whatsoever. Instead, raw q-space measurements are used directly without a model, only healthy population data is used for reference, and any deviations in a patient dataset from the healthy reference database are detected using novelty detection methods. This is done in each voxel independently, i.e. without spatial bias.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Model-free diffusion MRI; novelty detection